2022
DOI: 10.1002/pc.26716
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in interface engineering of carbon fiber reinforced polymer composites and their durability studies at different service temperatures

Abstract: A point of major concern in carbon fiber reinforced polymer (CFRP) composites is the interface between the carbon fibers (CFs) and the polymer matrix, which acts as the weakest link. Researchers have tried to work around this drawback by modifying the fiber or the matrix via the addition of nanofillers or using chemical treatment methods. In this review, the progress made in the last decade for enhancing the mechanical performance of CFRP composites by applying the aforementioned methods has been covered. Anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 209 publications
2
25
0
Order By: Relevance
“…In this context, graphene, carbon nanotubes (CNTs), and carbon black have become attractive nanomaterials as the reinforcement agents in polymer nanocomposites, [3][4][5][6][7][8] and as the filler materials in CFRP composites. [9][10][11][12] Graphene, when compared to CNTs, has a higher specific surface area, higher compatibility with the polymeric matrix, and unique two-dimensional honeycomb lattice structure, [13,14] and therefore has a higher potentiality to contribute mechanical, thermal and electrical properties of CFRP composites. In the recent works, it was shown that graphene-filled polymer matrix or graphene functionalized fiber surface in CFRP composites improved the fiber-matrix interface resulting in enhanced conductivity and mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, graphene, carbon nanotubes (CNTs), and carbon black have become attractive nanomaterials as the reinforcement agents in polymer nanocomposites, [3][4][5][6][7][8] and as the filler materials in CFRP composites. [9][10][11][12] Graphene, when compared to CNTs, has a higher specific surface area, higher compatibility with the polymeric matrix, and unique two-dimensional honeycomb lattice structure, [13,14] and therefore has a higher potentiality to contribute mechanical, thermal and electrical properties of CFRP composites. In the recent works, it was shown that graphene-filled polymer matrix or graphene functionalized fiber surface in CFRP composites improved the fiber-matrix interface resulting in enhanced conductivity and mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent works, it was shown that graphene-filled polymer matrix or graphene functionalized fiber surface in CFRP composites improved the fiber-matrix interface resulting in enhanced conductivity and mechanical strength. [9,15] Also, highly conductive graphene skinned CFRP composites were demonstrated as the promising materials because they offer tailoring electrical properties of the conductive mesh for lightning protection. [16,17] Qin et al [18] reported that flexural strength and through the thickness conductivity of graphene coated carbon fiber (CF)/epoxy composites were increased by a factor of 82% and 165%, respectively, as compared to those of non-coated CF/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Some researchers have tried to improve the temperature resistance by adding nanofiller, chemical treatments, modifications in matrices or the fiber surfaces. [13,14] Although, there are several research works which have studied about the behavior of FRP, specifically CFRP and glass-FRP (GFRP), at elevated temperatures, the databases about all different types of polymeric resins, fiber reinforcement methods, manufacturing and curing methods, are incomplete. [2,11,[14][15][16][17][18][19] Therefore, the mechanical behavior of FRP at elevated temperatures must be studied comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…The inherent strength of the SCFs contributed to the matrix strength and thus the strength of the composite. [71] Similarly, SCF in the epoxy matrix toughened the matrix by delaying crack propagation via various mechanisms such as crack pinning and bifurcation and other toughening mechanisms such as SCF pullout. [72][73][74][75] These strengthening and toughening effects of SCFs were carried over to CT, but the effects were diminished.…”
Section: Flexural Testing At In-situ Cryogenic Temperaturementioning
confidence: 99%